PERTUMBUHAN EKONOMI DI INDONESIA, VIETNAM, DAN FILIPINA: PERBANDINGAN DETERMINASI INVESTASI DAN TENAGA KERJA DALAM PERSPEKTIF DATA PANEL PERIODE TAHUN 1994–2023 - aji, dede; Aji Mardani, Dede; Delis Rahmawati (LPPM IAIT, 2025)
Economic growth is a crucial indicator for assessing a country's development success. Although Indonesia recorded the highest investment value, there is a disparity with Vietnam, which emerged as the country with the highest economic growth in 2022 among ASEAN nations. This phenomenon highlights the need for further research into the effectiveness of investment and labor in driving economic growth. This study aims to analyze the impact of investment and labor on economic growth in Indonesia, Vietnam, and the Philippines during the 1994–2023 period. The analysis was conducted both partially and simultaneously. Employing a quantitative approach with panel data regression, the Fixed Effect model was selected based on the results of Chow and Hausman tests. The research findings indicate that investment has a positive and significant partial effect on economic growth. Similarly, labor also demonstrates a positive and significant partial effect on economic growth. Furthermore, simultaneously, both investment and labor are proven to significantly influence economic growth. The regression model used exhibits good predictive power, with 70.49% of the variation in economic growth being explained by investment and labor. These findings underscore the importance of synergy between investment effectiveness and improved labor quality in fostering sustainable economic growth in the Southeast Asian region.